2013
DOI: 10.1186/1471-2369-14-131
|View full text |Cite
|
Sign up to set email alerts
|

The clinical status and survival in elderly dialysis: example of the oldest region of France

Abstract: BackgroundThe number of elderly (≥75 years) patients with end-stage renal disease (ESRD) has increased markedly, including in the Limousin region, which has the oldest population in France. We retrospectively compared outcomes in elderly and non-elderly ESRD patients who started dialysis during two time periods.MethodsBaseline clinical characteristics, care, and survival rates were assessed in 557 ESRD patients aged ≥75 and <75 years who started dialysis in 2002–2004 and 2005–2007. Survival curves and Cox prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…The prevalence of impaired mobility in patients reaching ESRD was 7%-34% among the included studies (32)(33)(34)(35)(36)(37)(38)(39). Nine studies addressed mobility, and all nine reported immobility to be significantly associated with a higher risk of mortality, independent of sex and calendar age (32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Association Of Functional or Cognitive Impairment And Frailtmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of impaired mobility in patients reaching ESRD was 7%-34% among the included studies (32)(33)(34)(35)(36)(37)(38)(39). Nine studies addressed mobility, and all nine reported immobility to be significantly associated with a higher risk of mortality, independent of sex and calendar age (32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Association Of Functional or Cognitive Impairment And Frailtmentioning
confidence: 99%
“…Nine studies addressed mobility, and all nine reported immobility to be significantly associated with a higher risk of mortality, independent of sex and calendar age (32)(33)(34)(35)(36)(37)(38)(39)(40). Mobility status was assessed in all studies by using data on whether the patient was dependent for transfers and walking without objectifying actual mobility (for instance, by measuring gait speed).…”
Section: Association Of Functional or Cognitive Impairment And Frailtmentioning
confidence: 99%
“…6,7 It was reported that improved initial clinical status of elderly end-stage renal disease (ESRD) patients and better preparation for dialysis was associated with increased survival. 8 Decreased functional capacity, sensory deficits, cognitive impairment and depression have frequently been found in hemodialysis (HD) patients [9][10][11] but only a few studies used comprehensive geriatric assessment (CGA) to evaluate HD patients. [11][12][13][14] CGA is a multidimensional procedure designed to evaluate an older person's physical health, functional ability, cognition and mental health, and socioenvironmental circumstances, as well as an extensive review of prescriptions.…”
Section: Introductionmentioning
confidence: 99%
“…With advancing age come challenges to maintaining the nutritional status of these patients. In contrast to the general population, for whom overnutrition or obesity is associated with increased cardiovascular disease (CVD) risk, in patients who are maintained on HD, malnutrition and malnutrition-inflammation complex syndrome are associated with poor outcome 1,2. According to many authors, a significant number of HD patients display some degree of malnutrition, and malnutrition has been identified as one of the most powerful predictors of outcome in HD patients 13.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to recognize and prevent malnutrition in this potentially fragile population. There are no special requirements for the assessment of nutritional status in the elderly – as with younger patients, a panel of tests should be carried out since no one test can adequately assess all aspects of nutritional status 2,3…”
Section: Introductionmentioning
confidence: 99%